EFISIENSI TEKNIS PADI VARIETAS UNGGUL BARU DAYANG MURATAN DI KABUPATEN MUSI RAWAS - Wahyuni, Nenny; Suryati, Nila; Hidayat, Hidayat; Ningsih, Verry Yarda; Mukhlis, Mukhlis (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
Rice (Oryza sativa L.) is a strategic food commodity in Indonesia that significantly contributes to national food security. This study was conducted to evaluate the efficiency of rice farming using the New Superior Variety Dayang Muratan in Musi Rawas Regency. The study was conducted from July to September 2025. The method used in this study was a survey with a sample of 100 respondents. To measure the technical efficiency of Dayang Muratan rice variety, Data Envelopment Analysis (DEA) Model was used. The results of the study showed that the pattern of production factor use in Dayang Muratan rice farming in Musi Rawas Regency did not fully follow technical recommendations, especially the dosage of phonska fertilizer and pesticides which were below the recommendations. Based on the DEA analysis, the average technical efficiency value of 0.760 indicates that farmers only achieved 76% of their maximum production potential. This 24% inefficiency indicates that the problem lies not only in technical recommendations at the farm level, but also related to the quality of mentoring services, access to appropriate inputs, and the managerial capacity of farmers in managing the combination of production factors.